2009
DOI: 10.1161/hypertensionaha.108.125807
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Transport in the Choroid Plexus and Salt-Sensitive Hypertension

Abstract: Abstract-To elucidate the role of epithelial sodium channels (ENaCs) and Na ϩ -K ϩ -ATPase in Na ϩ transport by the choroid plexus, we studied ENaC expression and Na ϩ transport in the choroid plexus. Lateral ventricle choroid plexuses were obtained from young male Wistar, Dahl salt-resistant (SS.BN13), and Dahl salt-sensitive (SS/MCW) rats on a regular (0.3%) or high-(8.0%) salt diet. The effects of ENaC blocker benzamil and Na ϩ -K ϩ -ATPase blocker ouabain on sodium transport were evaluated by measuring the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 38 publications
(72 reference statements)
3
41
0
Order By: Relevance
“…In addition, immunoreactivity was found in cuboidal epithelium of the choroid plexus and in the ventricular ependyma. Overall, the localization of ␣-, ␤-, and ␥-ENaC subunits within the rat hypothalamus was similar to previous reports (3,4). Here, we report a more detailed localization of ␣-, ␤-, and ␥-ENaC within the SON and PVN performed by confocal double immunocytochemistry, using specific antibodies against ENaC subunits and antibodies against VP-or OT-NP.…”
Section: Immunocytochemical Localization Of Enac Subunits In the Son supporting
confidence: 90%
See 1 more Smart Citation
“…In addition, immunoreactivity was found in cuboidal epithelium of the choroid plexus and in the ventricular ependyma. Overall, the localization of ␣-, ␤-, and ␥-ENaC subunits within the rat hypothalamus was similar to previous reports (3,4). Here, we report a more detailed localization of ␣-, ␤-, and ␥-ENaC within the SON and PVN performed by confocal double immunocytochemistry, using specific antibodies against ENaC subunits and antibodies against VP-or OT-NP.…”
Section: Immunocytochemical Localization Of Enac Subunits In the Son supporting
confidence: 90%
“…Therefore, without quantitative RT-PCR it is only appropriate to state here that these dissociated cells are confirmed as MNCs producing OT or VP. Of these MNCs, mRNA for ␣-ENaC was found in cells 1, 2, 4, and 5, mRNA for ␤-ENaC was found in cells 1 and 3, mRNA for ␥-ENaC was found in cells 5, 9, 10, and 11, and mRNA for MR was found in cells 1,3,5,6,10, and 11. In addition, cell 12, although it did not contain VP or OT mRNA, contained ␣-ENaC, ␥-ENaC, and MR.…”
Section: Single-cell Rt-pcr Detection Of Enac Subunits In the Mncsmentioning
confidence: 99%
“…22,34,35 Wang et al 36 showed the presence of ENaC in the choroid plexus and the ependyma of the anteroventral third ventricle, and reported that intracerebroventricular infusion of aldosterone increased blood pressure and intracerebroventricular infusion of benzamil blocked this increase. To our knowledge, there are no reports that have indicated the existence of ENaCs in bulbospinal RVLM neurons.…”
Section: Effect Of Enac On Bulbospinal Neurons In the Rvlmmentioning
confidence: 99%
“…2,44 Several studies that inhibited Na + /K + -ATPase with ouabain on the luminal side of the CPE found a decrease in CSF produc- A small contribution to luminal Na + extrusion is made by NBCe2, which cotransports HCO 3 -. The K-Cl -cotransporter, KCC4, a genetic relative of the bumetanide-sensitive Na + -K + -2Cl -cotransporter, NKCC1 (see below), which is inhibited by furosemide, secretes the majority of Cl -into the CSF lumen.…”
mentioning
confidence: 99%